The Dime - Kent, Kathleen 1953- (New York : Mulholland Books, Little, Brown and Company, 2017)
Betty Rhyzyk, Brooklyns toughest female police detective, relocates to rough-and-tumble Dallas, Texas, where she must contend with a group of unruly subordinates, a persistent stalker, a formidable criminal organization, and an unsupportive girlfriend.
Keywords: Women detectives; Fiction; Dallas (Tex.); Fiction; Detective and mystery fiction